2020
DOI: 10.1080/09546634.2020.1770170
|View full text |Cite
|
Sign up to set email alerts
|

Topical methotrexate in dermatology: a review of the literature

Abstract: Background: Systemic methotrexate (MTX) is a useful treatment for many dermatologic conditions, however, the risk of adverse events prevents its use in patients with minimal or localized disease. Topical application of MTX may be an option to avoid the systemic adverse effects of oral MTX. Objective:To assess what is known about the efficacy and safety of topical methotrexate.Methods: A search on Pubmed was conducted. There were no limits on publication date.Results: A total of 963 articles were discovered. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…IFN seems to be efficient not only as a systemic but also as a topical [20]. Topical MTX also turned out to be efficient in early-stage MF, indicating that systemic drugs may represent new therapeutic options for topical treatment [21,22]. Concerning systemic MTX, our trial showed that RR was much higher (82%) than reported in other trials with low-dose MTX, ranging from 33 to 58% [8,14,19,23].…”
Section: Discussionmentioning
confidence: 71%
“…IFN seems to be efficient not only as a systemic but also as a topical [20]. Topical MTX also turned out to be efficient in early-stage MF, indicating that systemic drugs may represent new therapeutic options for topical treatment [21,22]. Concerning systemic MTX, our trial showed that RR was much higher (82%) than reported in other trials with low-dose MTX, ranging from 33 to 58% [8,14,19,23].…”
Section: Discussionmentioning
confidence: 71%
“…Since then, topical methotrexate has been tried in several cases of mycosis fungoides and oral precancerous lesions and in 1 case of lymphomatoid papulosis. 3 Bergstrom et al 4 reported the case of a patient who moistened a 2.5-mg tablet of methotrexate with tap water and rubbed it onto a gauze, which he then applied daily on the newly formed papules. The treated lesions regressed within 2 to 3 days, whereas the untreated ones persisted for more than 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known toxicity signs of methotrexate include bone marrow suppression, hepatic fibrosis, cirrhosis, and both oral and gastrointestinal ulceration [ 43 , 44 ]. Topical application of methotrexate may help avoid the systemic adverse effects of oral methotrexate for psoriasis treatment [ 45 , 46 ]. Therefore, topical treatment for local inflammatory skin diseases is considered safer to use.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%